2017
DOI: 10.1002/cm.21353
|View full text |Cite
|
Sign up to set email alerts
|

Towards a molecular architecture of the centrosome in Toxoplasma gondii

Abstract: Toxoplasma gondii is the causative agent of toxoplasmosis. The pathogenicity of this unicellular parasite is tightly linked to its ability to efficiently proliferate within its host. Tachyzoites, the fast dividing form of the parasite, divide by endodyogeny. This process involves a single round of DNA replication, closed nuclear mitosis, and assembly of two daughter cells within a mother. The successful completion of endodyogeny relies on the temporal and spatial coordination of a plethora of simultaneous even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 115 publications
0
36
0
Order By: Relevance
“…In animal cells, the centrosome copy restriction is mainly achieved through the polo kinase PLK4, which regulates the recruitment of SAS6 to the centriole together with CEP192 and CEP152 (Fujita, Yoshino, & Chiba, ). However, homologues for PLK4, CEP192, CEP152, or STIL (a protein partner of SAS6) were not found in apicomplexan genomes (Morlon‐Guyot et al, ), suggesting that the regulation of centriole formation is performed by other proteins and pathways in these parasites. Protein targets of this kinase are not known, but its putative localisation at the PCM may point toward the phosphorylation of proteins located in this area, indicating a role in outer core centrosome copy restriction for the T. gondii PCM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In animal cells, the centrosome copy restriction is mainly achieved through the polo kinase PLK4, which regulates the recruitment of SAS6 to the centriole together with CEP192 and CEP152 (Fujita, Yoshino, & Chiba, ). However, homologues for PLK4, CEP192, CEP152, or STIL (a protein partner of SAS6) were not found in apicomplexan genomes (Morlon‐Guyot et al, ), suggesting that the regulation of centriole formation is performed by other proteins and pathways in these parasites. Protein targets of this kinase are not known, but its putative localisation at the PCM may point toward the phosphorylation of proteins located in this area, indicating a role in outer core centrosome copy restriction for the T. gondii PCM.…”
Section: Discussionmentioning
confidence: 99%
“…The T. gondii centrioles are arranged in parallel fashion, and their size is smaller than that of the mammalian centrioles (Dubremetz, ; Francia & Striepen, ). Moreover, a comprehensive bioinformatics search of eukaryotic centrosome protein homologues in apicomplexan genomes revealed that several of the eukaryotic centrosome components are missing in the T. gondii genome (Morlon‐Guyot, Francia, Dubremetz, & Daher, ). This highlights the possibility of the unique composition of the centrosome in apicomplexan parasites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphorylation of C-NAP1/Cep250 by NIMA kinase Nek2 promotes degradation of C-NAP1/Cep250 and results in splitting of the linked centrosomes 21 . Reciprocal BLAST analysis suggests that C-NAP1/Cep250 and rootletin orthologs are absent from the Toxoplasma genome 6 , however, the regulatory machinery might be conserved.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the centrioles are composed of nine singlet microtubules, smaller in size than mammalian centrioles, and the centriole pair is arranged in parallel rather than perpendicular 4 . Orthologs of many key components in the mammalian centrosome cannot be found in the Toxoplasma genome 6 . Even without canonical protein orthologs, recent studies have shown that a group of coiled-coil proteins localize to the centrosome and support proper karyokinesis and cytokinesis 78 .…”
Section: Introductionmentioning
confidence: 99%